Barriers in exclusive breastfeeding encountered by mothers in urban slum area of a metropolitan city - Zil Gala; Sonal Shetye; Deepika M. Sadawarte; Mrunali Autade (Journal of Family Medicine and Primary Care)
Background: Breastfeeding is considered the most important source of nutrients for the baby. But owing to ignorance, lack of education, and cultural norms, exclusive breastfeeding (EBF) is not done by majority of the mothers. Hence, this study is carried out to determine various barriers faced by the mothers that influenced their decision on EBF. Methods: A descriptive qualitative study was conducted among the mothers whose children were less than 1 year of age visiting a well-baby clinic and Immunisation OPD of Urban Health Centre catering to the Urban Slum of Malvani in the Metropolitan city of Mumbai. In-depth interviews (IDIs) were done with 17 participants from August to November 2022. Thematic analysis was conducted on the qualitative data obtained. Results: Four major themes were generated from the transcripts. They are –barriers and concerns faced by mothers to exclusively breastfeed, enablers/motivators, sources of knowledge regarding EBF, and breastfeeding practices. Various barriers faced by mothers were gaps in knowledge, maternal Illness, religious reasons, inadequate milk production, bias toward top feeds, lack of autonomy to take decisions, and cultural norms, while positive family support, good knowledge about breastfeeding, and a supportive home environment motivated mothers to exclusively breastfeed their infants. Sources of knowledge were identified to be doctors and health care workers, mothers/mothers-in-law, sisters, friends, and social media. Conclusions: There are various challenges as well as motivators identified for EBF. Barriers, such as gaps in knowledge, and the negative influence of social media can be improved upon by health education. Therefore, it is crucial to teach expectant mothers as well as families about breastfeeding. Additionally, we advise stepping up public health education initiatives to support breastfeeding.